Belgian expert consensus for tumor-agnostic treatment of NTRK gene fusion-driven solid tumors with larotrectinib. (January 2022) - Awada, Ahmad; Berghmans, Thierry; Clement, Paul M.; Cuppens, Kristof; De Wilde, Bram; Machiels, Jean-Pascal; Pauwels, Patrick; Peeters, Marc; Rottey, Sylvie; Van Cutsem, Eric
Graphical abstract: Highlights: NTRK fusions are the primary oncogenic driver of a broad range of adult and pediatric cancers. Though rare, NTRK fusions represent an important clinically actionable target. Larotrectinib was approved by the EMA for treatment of NTRK fusion-driven cancers. This consensus offers guidance for testing and treatment of NTRK fusion cancers with larotrectinib, a pan-Trk-inhibitor. Early screening of patients for NTRK fusions should be performed whenever possible. Larotrectinib should be considered as early as appropiate in the treatment sequence. Abstract: Fusions of NTRK (neurotrophic tyrosine receptor kinase) genes with 5′ partner genes can result in the expression of chimeric proteins that drive oncogenesis through ligand-independent kinase activation. Despite variable frequencies of NTRK fusions in different tumor types, the fact that they are common to a wide range of cancers raises the possibility of developing tumor-agnostic treatments specifically targeting NTRK fusion products, irrespective of tumor type. The first-generation Trk (tropomyosin receptor kinase) inhibitor, larotrectinib, was the first tumor-agnostic treatment of NTRK fusion-positive cancers in adults and children, to be approved in the European Union. This consensus, developed by a Belgian multidisciplinary expert panel, aims to highlight the unmet medical need associated to NTRK fusion-driven cancer treatment and, based on current knowledge of NTRK fusions and larotrectinib treatment outcome and safety, provide comprehensive guidance to oncologists regarding NTRK fusion-driven cancer diagnostics and the best use of larotrectinib in real-world clinical settings.